Antimicrobial use in a peri-urban smallholder poultry system, Kenya - Mutua, Florence K.; Kiarie, Gideon; Mbatha, M.; Onono, J.; Boqvist, Sofia; Kilonzi, Emily; Lindahl, Johanna F.; Lewerin, S.S. (2022)
Objective(s): Analyze distribution and current usage of veterinary drugs in peri-urban smallholder poultry systems, Kenya Materials and methods: Machakos and Kajiado counties were purposively selected for the study. A baseline survey involving poultry farmers was conducted. Additional data were collected through key informant interviews (KII). The questionnaire data were electronically captured using open data kit, downloaded as a MS Excel® file, and cleaned. The data were analyzed using both descriptive and thematic approaches. Results: A total of 100 farmers were interviewed. Majority (58%) were >50 years old and kept chicken (100%), ducks (17%) and turkeys (16%). Methods for drug package disposal included burning (65%), burying (10%), and in pit latrines (9%). Sharing of same drugs across livestock species was reported (11 of the 66 farmers who kept other livestock). A small percentage (9%) mentioned using drugs intended for humans in animal treatment. Antibiotics constituted 47% of the total drug records used by farmers (n=347); 24% were used within the previous one month (24%) and had been administered by farmers themselves (90%). Challenges associated with the distribution, access and disposal of veterinary products were highlighted by KII respondents. Conclusion: on-prudent use of antimicrobials is a driver for development of antimicrobial resistance (AMR) which has serious public health implications. This project is developing an ICT framework to improve AMU monitoring and address the current information gap on AMR.